2016
DOI: 10.1002/anie.201609929
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Deep Eutectic Solvents and Organolithium Reagent Partnerships: Chemoselective Ultrafast Addition to Imines and Quinolines Under Aerobic Ambient Temperature Conditions

Abstract: Shattering the long-held dogma that organolithium chemistry needs to be performed under inert atmospheres in toxic organic solvents, chemoselective addition of organolithium reagents to non-activated imines and quinolines has been accomplished in green, biorenewable deep eutectic solvents (DESs) at room temperature and in the presence of air, establishing a novel and sustainable access to amines. Improving on existing methods, this approach proceeds in the absence of additives; occurs without competitive enoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(66 citation statements)
references
References 27 publications
1
65
0
Order By: Relevance
“…What was thought impossible just a few years ago, an aerobic, sustainable, polar, organometallic chemistry, is now starting to look distinctly possible . Thus, we recently uncovered the potential of deep eutectic solvents (DESs) by utilizing the nontoxic and biorenewable ammonium salt choline chloride [ChCl, (Me 3 NCH 2 CH 2 OH) + Cl − ] as an unique and green reaction medium for chemoselective ketone alkylation/arylation with organolithium or Grignard reagents at room temperature under air (Scheme ) . Comparing these reactions in DESs with those in neat water revealed a kinetic activation in the former, favoring addition reactions over hydrolysis.…”
Section: Introductionsupporting
confidence: 85%
“…What was thought impossible just a few years ago, an aerobic, sustainable, polar, organometallic chemistry, is now starting to look distinctly possible . Thus, we recently uncovered the potential of deep eutectic solvents (DESs) by utilizing the nontoxic and biorenewable ammonium salt choline chloride [ChCl, (Me 3 NCH 2 CH 2 OH) + Cl − ] as an unique and green reaction medium for chemoselective ketone alkylation/arylation with organolithium or Grignard reagents at room temperature under air (Scheme ) . Comparing these reactions in DESs with those in neat water revealed a kinetic activation in the former, favoring addition reactions over hydrolysis.…”
Section: Introductionsupporting
confidence: 85%
“…Thus, advancing the fundamental knowledge on DES structuring, and solvent‐reagent interactions will be the key in order to make further progress in the synthetic applications of polar organometallics in these unconventional solvents. More recently, by expanding the scope of these type chemistry in DESs, Hevia and García‐Álvarez have reported the addition reaction of a wide range of organolithium reagents to non‐activated imines . In this study, better conversions are observed using a 1:2 mixture of ChCl and glycerol ( Gly ) (Scheme ).…”
Section: Introducing Deep Eutectic Solvents To Polar Organometallic Cmentioning
confidence: 69%
“…[142] Scheme 30. [155,156] Furthermore, palladium catalyzed C-C coupling reactions were performed in DES based on saccharides and DMU or urea, including the Stille, [157] Heck, Sonogashira, [158] and Suzuki [159] coupling. [142] As mentioned above, the Diels-Alder reaction was performed in Lewis-acidic ILs, namely [bpy][AlCl 4 ] and [emim][AlCl 4 ].…”
Section: Application In Organic Synthesismentioning
confidence: 99%